Analisis Financial Distress Dengan Metode Altman Sebagai Prediksi Kesehatan Keuangan Perusahaan: Financial Distress Analysis with the Altman Method as a Prediction of Company Financial Health - Nandini, Indira; Mudjiijah, Slamet (Efektor, 2023)
The research conducted has the aim of facilitating companies in obtaining information about the symptoms of Financial Distress to predict the financial health of a company. The research results can be used as a reference source of information for companies when in a condition of Financial Distress, companies need to anticipate and improve their financial performance. The secondary data used was obtained from www.idx.co.id and www.idnfinancials.com along with related company websites. The purposive sampling method is a sample selection technique using a descriptive quantitative approach in order to obtain 15 food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The analytical method is Altman Modification. The results of this study explain that in the Modified Altman method there are 11 companies in a healthy condition, 1 company in a gray area and 3 companies in the possibility of bankruptcy.